An Advanced Hierarchical Attribute Based Encryption Access Control in Mobile Cloud Computing - N.K, Sreelesh; Kumar B J, Santhosh (International Journal of Engineering and Technology, 2018)
Cloud computing is a revolutionary computing technique, by which computing resources are provided dynamically via Internet is widely popular. Since the most attractive part of cloud computing is computation outsourcing, it is far beyond enough to just conduct access control. Unfortunately, the data in the cloud is out of userâ€™s control in most cases, privacy risks would rise dramatically due to the access of unauthorized users. The security of the data is the major concern. Coordinating mobile devices into cloud computing is a rising but encouraging illustration. The coordination happens in a cloud based multi-layered client information sharing condition. With the coordination of cloud computing with mobile devices may result in security issues such as information privacy and client rights.The proposed work makes use of a technology using Advanced Hierarchical Attribute Based Encryption (A-HABE) architecture, in which the data storage will be in hierarchical structure and the retrieval of data will also be in the form of access level. Data confidentiality should be guaranteed and the system should be resilient. The secure storage and sharing of data without the fear of an unauthorized access in the cloud can result in growth in many sectors.Â